Suppression rather than activation of the integrated stress response (GCN2–ATF4) pathway extends lifespan in the fly - Miriam S. Götz; Dan J. Hayman; Gracie Adams; Fumiaki Obata; Mirre J. P. Simons (Proceedings of the National Academy of Sciences, 2026)
Stress response pathways are emerging as conserved modulators of lifespan. The prevailing hypothesis is that activation of stress-responsive pathways, including the amino acid deprivation arm of the integrated stress response (ISR; the GCN2–ATF4 pathway), is prolongevity. Activation of ATF4 orthologs extends lifespan in Saccharomyces cerevisiae and Caenorhabditis elegans , but its role in other longer-lived organisms remains unclear. We comprehensively tested the role of the GCN2–ATF4 pathway in longevity in the fly ( Drosophila melanogaster ) for the first time. We used conditional genetic manipulation of dGCN2 and its downstream effector Drosophila ATF4 ( crc ; dATF4 ). In contrast to previous studies, we show that overexpression of dGCN2 and dATF4 significantly reduces lifespan, while knockdown (in vivo RNAi) of dATF4 extends lifespan. We confirmed that dATF4 activity was successfully modulated using a fluorescent dATF4 activation reporter. Borrelidin, a tRNA synthetase inhibitor, significantly reduced lifespan in a both dATF4 and diet-dependent manner, independent of microbial load, showing our modulation of dATF4 altered nutrient to ISR signaling. We further conducted long-read RNA sequencing and found that our manipulation of dATF4 changed global transcription in opposite directions, including known ATF4 target genes. Enrichment analysis revealed that dATF4 overexpression may drive metabolic stress, while dATF4 knockdown may upregulate proteostasis and DNA repair pathways. Our work reveals that ATF4 may exhibit a dual, dose-, and context-dependent role in aging. Chronic dATF4 activation is detrimental in flies, while chronic suppression is prolongevity. The GCN2–ATF4 pathway thus qualifies as a modifiable control of lifespan with cross-species relevance.